Lie Reductions and Conservation Laws of a Coupled Jaulent-Miodek System - Muatjetjeja, Ben; Mogorosi, Tshepo. E. (Journal of Applied Nonlinear Dynamics, 2026)
Symmetry analysis is performed on a coupled Jaulent-Miodek system, which arises in many branches of physics such as particle physics and fluid dynamics. The similarity reductions and new exact solutions are constructed. Subsequently, conservation laws are derived using the multiplier approach.